Impact of food safety training on the knowledge, practice, and attitudes of food handlers working in fast-food restaurants. Issue 4 (1st April 2019) - Elobeid, Tahra; Savvaidis, Ioannis; Ganji, Vijay
Abstract : Purpose: In many developing countries, the main source of food related illness is the fast foods restaurants. Health inspections of fast-food restaurants may not be sufficient to ensure and enforce the food safety regulations. The purpose of this paper is to investigate the food safety knowledge, attitudes and practices (KAP) of fast food handlers in Qatar. Design/methodology/approach: Data were collected from 102 fast-food handlers through a structured survey. The questionnaire comprised questions on food safety KAP. The association between scores for KAP among the food handlers was measured with Spearman's rank correlation. Findings: A significant direct association was found throughout the different criteria of food safety KAP. In total, 90 percent of fast food handlers had undergone formal training on food safety. Although fast food handlers thought they had overall good knowledge on food safety (93.9 percent), results showed that they had a poor knowledge on proper cleaning of equipment, cross-contamination, foodborne diseases, food danger zone and correct procedures for thawing of frozen food. Only (34.7 percent) of the food handlers correctly identified Salmonella as a food pathogen. Originality/value: Based on the current findings, the authors believe that continuous food safety and hygiene training should be implemented in all food service operations especially in fast-food restaurants in Qatar to ensure that all food handlers have the knowledge and the skill to provide safe food.